Generation a shared secret using artificial neural networks - U. F. Holikau; M. L. Radziukevich (Системный анализ и прикладная информатика, 2019)
In the Kanter’s and Kinsella’s works is proposes the use of two synchronized artificial neural networks (SANN) connected by opening communication channel to confidential formation of a common cryptographic key. At the same time, there are few questions of practical suitability of this technology for cryptographic applications. There are no recommendations on the choice of parameters of the used networks, ensuring acceptable speed and guaranteed confidentiality of the generated general secret.In this regard, it is interesting to substantiate the rational values of the parameters of ANN from the point of view of cryptographic requirements and security analysis of the proposed method of formation of cryptographic keys.